Development of risk communication strategies to improve control of Cysticercosis bovis in North Central Namibia - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.